Petroelastic modeling of carbonate reservoirs in the view of different void types - Ya. S. Grigoryan; I. O. Bayuk (Известия высших учебных заведений: Геология и разведка, 2022)
Background. Fractures present in carbonate rocks facilitate fluid flow within void spaces. Each type of voids can have a different effect on rock elastic properties, which, in turn, allow the characteristics of voids to be estimated by assessing the velocity of elastic waves. In this paper, an effect of pores and fractures on the velocity of elastic waves is analyzed by petroelastic modeling. An example of solving an inverse problem is presented, involving the determination of fracture porosity and relative fracture opening using the data on elastic wave velocity and hydrocarbon reservoir density obtained during geophysical well logging.Aim. To increase the accuracy of experimental data on the velocity of elastic waves that propagate across hydrocarbon carbonate reservoirs by assessing the pore and fracture characteristics of voids.Materials and methods. The effective medium theory was used as an efficient way to evaluate physical, including elastic, properties based on rock composition and microstructure. Using Berryman’s self-consistent method, we created a model of rock elastic properties, or a petroelastic model, the void space in which was represented by isometric pores and fractures. This model was applied to a well in a petroleum province in West Siberia.Results. The effect of characteristics determining the void space of porous-fractured rocks on the velocity of elastic waves was defined. Velocity surfaces were constructed in accordance with changing parameters of the model, i.e. fracture porosity and fracture aspect ratio. The obtained theoretical and experimental data were compared in order to determine fracture development zones and to evaluate volume concentration and relative fracture opening in these zones.Conclusion. The effect of pores and fractures on elastic wave velocity in porous-fractured carbonate reservoirs was studied by petroelastic modeling. The zones of excessive fracturing were defined and the parameters of volume concentration and relative fracture opening were determined using the data obtained by geophysical well logging in a petroleum province in West Siberia.